Autophagy modulation as a potential targeted cancer therapy: From drug repurposing to new drug development. Issue 3 (26th January 2021) - Lin, Chia‐Jung; Tsao, Yuan‐Ni; Shu, Chih‐Wen
Abstract: Autophagy is an evolutionarily conserved signaling pathway to deliver dysfunctional proteins or organelles into lysosomes for degradation and recycling, which is an important pathway for normal homeostasis. Autophagy dysfunction can lead to various diseases, particularly cancer. Autophagy not only plays a role in tumor suppression, but it also serves as a tumor promoter in cancer malignancy. In this review, we summarize the involvement of autophagy‐related (ATG) proteins in autophagy signaling and the role of autophagy in cancer progression. The effectiveness of US Food and Drug Administration‐approved drugs in regulating autophagic flux and suppressing cancer cells is also discussed. Moreover, since clinically available drugs do not specifically target ATG proteins, there is little doubt that their cancer suppression function is autophagy dependent. Therefore, this review also discusses several inhibitors against ATG proteins, such as ULK1/2, ATG4, and VPS34 to suppress cancer cells. Autophagy modulators can be either used alone or combined with chemotherapy or radiation therapy to enhance the efficacy of current treatments for certain types of cancer. This review summarizes current autophagy modulation used as a potential strategy for targeted cancer therapy.